Dynamics of trace and rare earth elements during long-term (over 4 years) decomposition in Scots pine and Norway spruce forest stands, Southern Sweden - Gautam, Mukesh K.; Berg, Björn; Lee, Kwang-Sik; Nilsson, Torbjörn; Shin, Hyung Seon (Frontiers in Environmental Science, 2023)
The temporal dynamics of 33 major, trace, and rare earth elements (REEs) were studied in the litter samples containing Swedish Norway spruce (Picea abies) (NSL) and Scots pine (Pinus sylvestris) (SPL), with the aim to assess their release and accumulation dynamics. Litter bags (8 × 8 cm) were incubated in paired monoculture stands with both the species for up to 5 years from 1979 to 1984 according to a randomized block design comprising 25 blocks (1 × 1 m) within an area of 625 m2. The decomposition rate was slightly higher for Scots pine litter (k = 0.315) than for Norway spruce litter (k = 0.217). During litter decomposition, at ∼70% accumulated mass loss (AML), the concentration of trace elements increased by >50% in both litter types compared to initial concentrations. The concentration change took place in a non-linear pattern, and polynomial quadratic regression between concentration change and accumulated mass loss resulted in significant relationships (adj R2 = 0.20–0.97; p = 0.15–<0.0001). The changes in concentration and amount of trace elements resulted in two main types of dynamics: 1) both concentration and amount increased for Fe, Al, Ti, Cu, Mo, V, Zr, Sb, As, Cs, Pb, Th, and U; 2) concentration increased but amount decreased for Ni, Zn, Li, and Sr. The amount of REEs increased from ∼3-fold to 99-fold from the beginning to the end of incubation, suggesting accumulation during litter decomposition. The dynamics of different REEs were similar in their change patterns in the two litters. Different REEs had generally identical change patterns during incubation, which is reflected in the high correlations among them (r2 = >0.95). A general upward convexity in the dynamics suggests that if further incubated in the field, decomposing litter could have accumulated more REEs in the organic matter. The results of this study can be useful for future studies in other ecosystems including metal-contaminated sites or element-depleted sites. Plant litter accumulation, its decomposition, and build-up of humic substances in the decomposing organic matter can act as a sink for elements and can be used as a management tool for ecological amelioration of metal-contaminated sites as well as natural systems that are impoverished, especially recuperating sites. The study’s findings have implications beyond such sites and can be useful in any research that seeks to understand the patterns of accumulation and release related to decomposition in different ecosystems.